The U.S.’ Coercive Diplomacy toward China in 2025 and the Future Prospects of Its Strategic Coercive Diplomacy - Quoc, Dung Nguyen; Minh, Trang Nguyen (Theoretical and Practical Research in Economic Fields; Vol 16 No 4 (2025): TPREF Special Issue, Volume XVI, Issue 4(36), Winter 2025DO - 10.14505/tpref.v16.4(36).09, 2025)
This research conducted a comprehensive analysis of Washington’s strategic application of coercive diplomacy toward Beijing, focusing on three principal dimensions: political, economic, and military. Grounded in the theoretical frameworks of coercive diplomacy, the Truman Doctrine, and “Trump’s Transactional Diplomacy,” the study employed a hybrid methodology combining content and event data analysis to examine diplomatic behaviors, political statements, tariff policies, technological measures, and military maneuvers enacted by the Trump 2.0 administration. First, Washington utilized coercive measures to reaffirm its global superiority over China. Domestic self-reliance initiatives, such as the AI Action Plan, aimed to demonstrate that U.S. endogenous capabilities remained competitive with China’s manufacturing infrastructure. Second, the strategic deployment of its alliance system underscored America’s intent to assert leadership over a globally integrated network of political, economic, and defense partnerships, contrasting with China’s comparatively modest coalition. Third, coercive diplomacy extended beyond Sino-American dynamics; the Trump administration applied similar pressure tactics toward strategic partners worldwide, often leveraging economic dominance through tariff threats. Strategically, coercive diplomacy toward China appeared poised to become a long-term doctrine, as countering Beijing represented one of the few bipartisan convergences in U.S. politics. In response, China was expected to reinforce domestic resilience and alliance-building to prepare for sustained confrontation. This rivalry was likely to trigger the most extensive multidimensional competition in modern history. Developing nations must adopt proactive, neutral diplomacy to strengthen internal capacities, while they should avoid positioning themselves as adversaries to either superpower.